At last an issue : comments on the 1991 general elections in Montserrat. - FERGUS, Howard A. (1993)
Provides basic data on the 1991 General Elections and offers analytical comments on certain features of the electoral process. Focuses on the issue of morality and the integrity of persons holding political office.